1999
DOI: 10.1002/(sici)1097-4644(19991215)75:4<555::aid-jcb2>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Binding of nuclear proteins to an upstream element involved in transcriptional regulation of the testis-specific histone H1t gene

Abstract: The testis-specific histone H1t is synthesized during spermatogenesis exclusively in late pachytene primary spermatocytes. Transcription of the H1t gene is repressed in every tissue except testis. Within the testis, transcription is repressed during development before the spermatocyte stage and in later stages of germinal cell maturation. Mechanisms involved in transcriptional repression of the H1t gene are unknown. To assess the contribution of upstream H1t promoter sequence to transcriptional silencing in no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…The TE/GC-box is methylated in tissues where H1t is not expressed but is unmethylated in spermatocytes (Wilkerson et al 2002b), and another proximal GC-rich region (GCbox2) is also involved in H1t silencing (Clare et al 1997a, b). A distal region located between −948 and −780 bp also functions as a silencer (Wolfe and Grimes 1999). ChIP experiments in mice have identified that the BET doublebromodomain-containing protein Brdt binds to this silencer and represses H1t expression (Shang et al 2007).…”
Section: Transcriptional and Translational Regulationmentioning
confidence: 99%
“…The TE/GC-box is methylated in tissues where H1t is not expressed but is unmethylated in spermatocytes (Wilkerson et al 2002b), and another proximal GC-rich region (GCbox2) is also involved in H1t silencing (Clare et al 1997a, b). A distal region located between −948 and −780 bp also functions as a silencer (Wolfe and Grimes 1999). ChIP experiments in mice have identified that the BET doublebromodomain-containing protein Brdt binds to this silencer and represses H1t expression (Shang et al 2007).…”
Section: Transcriptional and Translational Regulationmentioning
confidence: 99%
“…In this study we examined transcription by using a histone H1t promoted reporter vector Pst-pGL3 in transient expression assays. This expression vector, containing a short histone H1t promoter that extends 141 base pairs (bp) upstream from the transcription initiation site to the PstI site and lacking the upstream silencer element, is active in initiating transcription in several nongerminal cell lines [7].…”
Section: Methylation Represses Expression Of the Histone H1t Gene In mentioning
confidence: 99%
“…Studies show that H1 histones can interact with components of the transcription initiation complex to block transcription [3,5]. Our laboratory has examined the testis-specific histone H1t variant gene to determine mechanisms of regulation of expression of this gene [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Wolfe et al [31,42] reported a silencer activity of approximately threefold in the Ϫ780 to Ϫ948 region using transient transfection in the mouse mammary C1271 cell line. We did not observe a distinct silencer activity in this region, and it may be that separate silencer elements are active in specific cell lines.…”
Section: Cap-proximal Silencermentioning
confidence: 99%